2005
DOI: 10.1177/00238309050480010101
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Native- and Second-Language Vowel System(s) in Early and Late Bilinguals

Abstract: The objective of this study was to determine how bilinguals' age at the time of language acquisition influenced the organization of their phonetic system(s). The productions of six English and five Korean vowels by English and Korean monolinguals were compared to the productions of the same vowels by early and late Korean-English bilinguals varying in amount of exposure to their second language. Results indicated that bilinguals' age profoundly influenced both the degree and the direction of the interaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
159
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(173 citation statements)
references
References 34 publications
12
159
1
1
Order By: Relevance
“…Finally, the result of this study is consistent with that of Baker and Trofimovich (2005) who found that late bilinguals tended to rely mostly on their L1 sound category in the process of L2 production, however, in their study, early bilinguals seem to establish a new sound category for L2 contrasts distinct from their L1, which helps the early bilinguals perform more proficient L2 production. Although the late bilinguals in this study and in Baker and Trofimovich (2005)'s research have a certain amount of L2 experience, their L2 experience plays very little of a role in L2 acquisition.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Finally, the result of this study is consistent with that of Baker and Trofimovich (2005) who found that late bilinguals tended to rely mostly on their L1 sound category in the process of L2 production, however, in their study, early bilinguals seem to establish a new sound category for L2 contrasts distinct from their L1, which helps the early bilinguals perform more proficient L2 production. Although the late bilinguals in this study and in Baker and Trofimovich (2005)'s research have a certain amount of L2 experience, their L2 experience plays very little of a role in L2 acquisition.…”
Section: Discussionsupporting
confidence: 90%
“…Although the late bilinguals in this study and in Baker and Trofimovich (2005)'s research have a certain amount of L2 experience, their L2 experience plays very little of a role in L2 acquisition. This showed that L2 learners' age plays a substantial role in the relationship between L2 experience and a successful L2 acquisition.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations